Effects of the vertical heterogeneity on the gas production behavior from hydrate reservoirs simulated by the fine sediments from the South China Sea. (15th September 2022) - Shi, Kangji; Wang, Zifei; Jia, Yuxin; Li, Qingping; Lv, Xin; Wang, Tian; Zhang, Lunxiang; Liu, Yu; Zhao, Jiafei; Song, Yongchen; Yang, Lei
Abstract: There have been several field tests worldwide to recover natural gas from marine gas hydrate reservoirs. The resulting intrinsic characteristics of the sediments are recognized as the major challenge hindering the large-scale gas production; of particular interest is the heterogeneous spatial distribution of natural gas hydrates in the sediments. Open issues still remain on mimicking the locally varying reservoir and revealing its role in the production process. Here in this work, reservoirs with a heterogeneous distribution of gas hydrates were prepared by controlling the uneven distribution of moisture in the fine natural sediments drilled from the South China Sea; special interest was put in the effects of the well location and depressurization schemes on the gas production performance. The results showed that the production efficiency in the heterogeneous reservoirs was significantly weakened compared with the homogeneous case; this was ascribed to the ununiform distribution of methane hydrates and pore fluids and a resulting locally different energy demand. Consequently, the production behavior showed a strong dependence on the depressurization location. A wellbore arranged in the layer with a high permeability can help improve the gas production efficiency by up to 38.25%. This yet resulted in an uneven temperature distribution; the rapid gas production and methane hydrate dissociation decreased the reservoir temperature to −3.33 °C. Further applying a cycling and step-wise depressurization could raise the minimum reservoir temperature up to 1.12 °C. Whereas, relieving temperature decline only through consuming the sensible heat in the reservoir and the surroundings was found to seriously weaken the gas production rate; an external heat supply was thus suggested in the hydrate-abundant regions for efficient gas production. Our findings expand the understanding of the spatially varying gas production behavior from the vertically heterogeneous hydrate-bearing fine marine sediments and may guide the operation of well location and depressurization schemes for field production in similar reservoirs. Graphical abstract: Image 1 Highlights: Heterogeneous hydrate samples were prepared by unevenly distributing the moisture. Production behavior from the vertically heterogeneous hydrate reservoir was studied. The optimized wellbore location would increase the production efficiency by 38.25%. Heat supply was suggested in the hydrate-rich area to compensate the sensible heat.